The influence of the project based learning model on student knowledge based on science process skills (KPS) viewed from student learning motivation - Rizki Maulida; Jane Elnovreny; Erwin Ginting (Institute of Computer Science (IOCS), 2023)
This research is a quasi-experimental research. This research aims to look at students' science process skills using the Project Based Learning (PjBL) learning model in terms of student motivation. This research was conducted at Potenti Utama University with the research sample being Industrial Engineering students in class A and B odd semester FY 2023 – 2024. The results of this research arelearning using the PjBL learning model has an average difference value of 27.90, while in the control class it is 12.37. This shows that there is an increase in students' Science Process Skills in the experimental class compared to the control class. The difference in Science Process Skills of students in the experimental class is 29.00 for classes with low learning motivation and 43.00 for high learning motivation. Meanwhile, the control class for students' Science Process Skills was 23.00 for students with low learning motivation, and 39.00 for students with high learning motivation. This shows that there is a relationship between student learning motivation and Science Process Skills. Based on the test results using SPSS, it can be seen that the F-count value is 4.86. The calculated F result obtained compared with the F table at N = 38 is 4.10 with a significance level of 0.05. The calculated F results obtained are greater than the F table (4.86 > 4.10). Thus it can be concluded that it is accepted and rejected. So it can be said that there is a significant influence of the PjBL learning model on science process skills (KPS).